Melatonin Regulates Chloroplast Protein Quality Control via a Mitogen-Activated Protein Kinase Signaling Pathway - Hyoung Yool Lee; Kyoungwhan Back (MDPI AG, 2021)
Serotonin N-acetyltransferase 1 (SNAT1), the penultimate enzyme for melatonin biosynthesis has shown N-acetyltransferase activity toward multiple substrates, including histones, serotonin, and plastid proteins. Under two different light conditions such as 50 or 100 μmol m−2 s−1, a SNAT1-knockout (snat1) mutant of Arabidopsis thaliana ecotype Columbia (Col-0) exhibited small size phenotypes relative over wild-type (WT) Arabidopsis Col-0. Of note, the small phenotype is stronger when growing at the 50 μmol m−2 s−1, exhibiting a dwarfism phenotype and delayed flowering. The snat1 Arabidopsis Col-0 accumulated less starch than the WT Col-0. Moreover, snat1 exhibited lower Lhcb1, Lhcb4, and RBCL protein levels, compared with the WT Col-0, but no changes in the corresponding transcripts, suggesting the involvement of melatonin in chloroplast protein quality control (CPQC). Accordingly, caseinolytic protease (Clp) and chloroplast heat shock proteins (CpHSPs), two key proteins involved in CPQC, as well as ROS defense were suppressed in snat1. In contrast, exogenous melatonin treatment induced expression of Clp, CpHSP, APX1, and GST, but not other growth-related genes such as DWF4, KS, and IAA1. Finally, the induction of ClpR1, APX1, and GST1 in response to melatonin was inhibited in the mitogen-activated protein kinase (MAPK) knockdown Arabidopsis (mpk3/6), suggesting that melatonin-mediated CPQC was mediated, in part, by the MAPK signaling cascade. These results suggest that melatonin is involved in CPQC, which plays a pivotal role in starch synthesis in plants.